Caput Castellae. Burgos ciudad de mercaderes. - Camarero Bullóin, Concepción (Boletín de la Real Sociedad Geográfica, 2022)
En este trabajo se estudia cómo Burgos, desde el pequeño núcleo nacido en el siglo ix como parte del sistema defensivo de la frontera del Duero en plena Reconquista, evoluciona hasta ser en el siglo xvi una ciudad rica, boyante e internacional, cuyos mercaderes comercian por toda Europa, controlan el mercado de los seguros y financian a concejos y coronas. ABSTRACT In this work we study how Burgos, from the small nucleus born in the 9th century as part of the defensive system of the Duero river border in the middle of the Reconquest, become into a rich, buoyant and international city in the 16th century, whose merchants trade for all over Europe, they control the insurance market and finance councils and crowns.